Academic Benefits of Electronic Resources: A Study of University Library Users in Bihar (LIS TODAY, 2026)
This study looks into how university library users in Bihar, India, can use electronic tools to help them with their studies. A survey of 450 users from six of the state’s largest universities was conducted using a mix of tools. The study examines how people use electronic tools, what problems they seem to cause, and how they affect academic performance. The results show that 78.4% of those who responded usually use electronic resources. These resources make research faster (86.2%), give people access to up-to date information (91.3%), and make people more productive overall (74.8%). However, problems like not knowing how to use technology (42.1%) and not being able to connect to the internet (38.7%) still exist. The study adds to the growing body of research on digital academic resources in developing areas and makes suggestions for how to improve the use of electronic resources in Bihar’s university libraries.
Keywords: Electronic resources, academic libraries, university users, Bihar, digital literacy, information access